Biodiesel production from waste cooking oil via single steps tranesterification process with the aid of sodium methoxide as a catalyst - Mohd Ghadafi, Ismail (2008)
Biodiesel popularly known as an alternative diesel fuel in developed countries mainly for transportation and agriculture industry. Now days, biodiesel became more important due to insufficient of petroleum fuel and the needs of environmental friendly energy sources. The high price of crude petroleum oil to has made biodiesel become more favorable in the market. Due to the high cost of raw material, waste cooking oil use as raw material instead of conventional method using vegetable oil. However, waste cooking oil contain high amount of free fatty acid and thus, single steps transesterification process with the aid of homogeneous catalyst were implemented in this experiment with sodium methoxide is use as homogeneous catalyst. Methanol was chosen as alcohol solvent because its price is more cheaper compare to others type of alcohol. In the transesterification process, the triglycerides will react with a methanol to form esters and a by product glycerol. In this experiment, Response surface methodology (RSM) was used to studies the effect of two variables which are reaction time (varied from 30 minutes to 90 minutes) and catalyst concentrations (0.5 wt.% to1.0 wt%). The oil to methanol ratio was fixed at 1:6 and temperature was fixed at 65oC. The sample of each experiment was analyzed using thin layer chromatography (TLC) and the yield of biodiesel was recorded. The optimal reaction condition to achieve highest methyl ester content was at reaction time 70.15 minutes and catalyst concerntration was at 1.50wt.% while the optimal reaction condition to achieve highest biodiesel yield was at reaction time 64.66 minutes with the catalyst concerntration of 0.92wt.%.